Intra‐Articular Administration of Autologous Micro‐Fragmented Adipose Tissue in Dogs with Spontaneous Osteoarthritis: Safety, Feasibility, and Clinical Outcomes. (23rd July 2018) - Zeira, Offer; Scaccia, Simone; Pettinari, Letizia; Ghezzi, Erica; Asiag, Nimrod; Martinelli, Laura; Zahirpour, Daniele; Dumas, Maria P.; Konar, Martin; Lupi, Davide M.; Fiette, Laurence; Pascucci, Luisa; et al.
Abstract: Similar to the disease affecting humans, osteoarthritis (OA) is a painful musculoskeletal condition affecting 20% of the adult canine population. Several solutions have been proposed, but the results achieved to date are far from being satisfactory. New approaches, such as intra‐articular delivery of cells (including mesenchymal stromal cells), have been proposed. Among the many sources, the adipose tissue is considered very promising. We evaluated the safety, feasibility, and efficacy of a single intra‐articular injection of autologous and micro‐fragmented adipose tissue (MFAT) in 130 dogs with spontaneous OA. MFAT was obtained using a minimally invasive technique in a closed system and injected in the intra‐ and/or peri‐articular space. Clinical outcomes were determined using orthopedic examination and owners' scores for up to 6 months. In 78% of the dogs, improvement in the orthopedic score was registered 1 month after treatment and continued gradually up to 6 months when 88% of the dogs improved, 11% did not change, and 1% worsened compared with baseline. Considering the owners' scores at 6 months, 92% of the dogs significantly improved, 6% improved only slightly, and 2% worsened compared with baseline. No local or systemic major adverse effects were recorded. The results of this study suggest that MFAT injection in dogs with OA is safe, feasible, and beneficial. The procedure is time sparing and cost‐effective. Post injection cytological investigation, together with the clinical evidence, suggests a long‐term pain control role of this treatment. The spontaneous OA dog model has a key role in developing successful treatments for translational medicine.Stem Cells Translational Medicine 2018;7:819–828 Abstract : Treatment of osteoarthritis by intra‐ and/or peri‐articular injection of autologous and micro‐fragmented adipose tissue (MFAT). This minimal manipulation technique intra‐operatively provides MFAT in a short time, without expansion or enzymatic treatment providing the key elements to support a natural reparative response: scaffold (the adipose tissue structure), cells (ASCs), and growth factors (secreted cytokines and chemokines) with anti‐inflammatory and reparative properties.